PENGARUH BERKUMUR AIR REBUSAN DAUN JAMBU BIJI TERHADAP INDEKS PLAK PADA MURID SDN 10 KUBU AMPEK ANGKEK KABUPATEN AGAM - Ika Ifitri; Eriyati Eriyati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
INTRUDUCTION: The main cause of dental and oral health problems is periodontal disease. This desease is caused by bacteria that accumulate in dental plaque. It necessary to prevent the plaque, according to some research states that essential oils can increase the activity of inhibition of plaque. Oil astsiri contained in many plants, one of them in guava leave. The purpose of this study is to determine the effect of rinsing with guava leaf water to plaque formation. RESEARCH METHOD: This research uses quasi experiment research that is giving the gargling treatment by decoction of guava leaf towards experiment group after its plaque at zero. The number of samples of 30 people was taken by random sampling technique. Data analysis with independent test with p